DEVOTION, FESTIVITY AND SETTLEMENT PROCESS IN THE BORDERS OF THE NEW KINGDOM OF GRANADA 1650-1800 - Jiménez Meneses, Orián (2017)
This article presents the impact that the devotion and religious holidays had in the settlement process of Antioquia between 1650 and 1800. The text came from the research of “El arco iris de la paz” (“The Peace Rainbow”), written in order to get a doctorate in History. Based on the research of  handwritten sources, the settlement process is related to religious devotion, and it was studied how the transfer of the image of “Nuestra Señora del Rosario” (“ Our Lady of Rosary “) broke out  a conflict in the mid-eighteenth century , between the city of Arma, belonging to the jurisdiction of Popayan , and the people of Rionegro in Antioquia territory . In this paper is shown that the devotions and religious holidays were an overwhelming way to consolidate the models and patterns of a settlement process in the New Kingdom of Granada.